Sleep-related laryngospasm - Flavio S. Aloe; Michael J. Thorpy (Arquivos de Neuro-Psiquiatria)
Seven patients (mean age 46.6; range 33-58; 6M.1F) presented with sleep-related choking episodes and were found to have features in common that distinguished them from other known causes of choking episodes during sleep. The characteristic features include: an awakening from sleep with an acute choking sensation, stridor, panic, tachycardia, short duration of episode Gess than 60 seconds), infrequent episodes (typically less than 1 per month), and absence of any known etiology. The disorder most commonly occurs in middle-aged males who are otherwise healthy. In one patient an episode of laryngospasm was polysomnographically documented to occur during stage 3. The clinical features and the polysomnographic findings suggest spasm of the vocal cords of unknown etiology.